PENDIDIKAN ISLAM DAN MUNCULNYA GERAKAN SOSIAL ISLAM INDONESIA - Aniek Rahmaniah (el-hikmah, 2011)
Since the New Order regime collapsed in 1998, the face of Indonesian Islam became increasingly complex. This is because the various manifestations of Islam in Indonesia, both as a political force as well as social and strength. The complexity of Islam after the New Order was also more pronounced because the process of development and change in terms of thought and forms of movement. In addition, Indonesian Islam witnessed the birth of the new educated middle class well to intensive contact with the ideas of modernity. Thanks to the development of Islamic educational institutions, the Muslims whether they are socio-cultural background and traditional and modern religious alike have the opportunity to tap into a new pattern of Indonesian life.